Identify metabolism-related genes IDO1, ALDH2, NCOA2, SLC7A5, SLC3A2, LDHB, and HPRT1 as potential prognostic markers and correlate with immune infiltrates in head and neck squamous cell carcinoma - Li, Ce; Chen, Shuai; Jia, Wenming; Li, Wenming; Wei, Dongmin; Cao, Shengda; Qian, Ye; Guan, Rui; Liu, Heng; Lei, Dapeng (Frontiers in Immunology, 2022)
Hypopharyngeal squamous cell carcinoma (HSCC) is a kind of head and neck squamous cell carcinoma (HNSCC) with poor prognosis. Metabolic reprogramming may regulate the tumor microenvironment (TME) by adapting quickly to cellular stress and regulating immune response, but its role in HSCC has not been reported. We used the nCounter® Metabolic Pathways Panel to investigate metabolic reprogramming, cellular stress, and their relationship in HSCC tissues and adjacent normal tissues. Metabolism-related pathways nucleotide synthesis and glycolysis pathways were significantly upregulated, while amino acid synthesis and fatty acid oxidation pathways were significantly downregulated in HSCC tissues compared to adjacent normal tissues. There is a significant correlation between metabolism-related pathways and cellular stress pathways. Enrichment of immune cell and tumor infiltrating lymphocyte (TIL) analysis showed changes in immune responses between HSCC tissues and adjacent normal tissues. Overall survival analysis showed that upregulated genes CD276, LDHB, SLC3A2, EGFR, SLC7A5, and HPRT1 are potential unfavorable prognostic markers in HNSCC, while downregulated genes EEA1, IDO1, NCOA2, REST, CCL19, and ALDH2 are potential favorable prognostic markers in HNSCC. Moreover, metabolism-related genes IDO1, ALDH2, NCOA2, SLC7A5, SLC3A2, LDHB, and HPRT1 are correlated with immune infiltrates in HNSCC. These results suggest that metabolic reprogramming occurs and correlates with cellular stress and immune response in HSCC, which may help researchers understand mechanisms of metabolic reprogramming and develop effective immunotherapeutic strategies in HNSCC.